2015
DOI: 10.1186/s12931-015-0274-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled carbon monoxide protects time-dependently from loss of hypoxic pulmonary vasoconstriction in endotoxemic mice

Abstract: BackgroundInhaled carbon monoxide (CO) appears to have beneficial effects on endotoxemia-induced impairment of hypoxic pulmonary vasoconstriction (HPV). This study aims to specify correct timing of CO application, it’s biochemical mechanisms and effects on inflammatory reactions.MethodsMice (C57BL/6; n = 86) received lipopolysaccharide (LPS, 30 mg/kg) intraperitoneally and subsequently breathed 50 ppm CO continuously during defined intervals of 3, 6, 12 or 18 h. Two control groups received saline intraperitone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
(96 reference statements)
2
6
0
Order By: Relevance
“…In line with other studies, a strong HPV was found in buffer-perfused isolated mouse lungs of healthy animals [ 14 , 15 ]. Consistent with previous experiments, a distinctive reduction of HPV was observed in lungs of endotoxemic mice [ 4 , 16 ]. It has been shown that HPV is modulated by several vasoactive mediators including nitric oxide and arachidonic acid metabolites, but the precise mechanisms mediating HPV are still incompletely understood [ 15 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with other studies, a strong HPV was found in buffer-perfused isolated mouse lungs of healthy animals [ 14 , 15 ]. Consistent with previous experiments, a distinctive reduction of HPV was observed in lungs of endotoxemic mice [ 4 , 16 ]. It has been shown that HPV is modulated by several vasoactive mediators including nitric oxide and arachidonic acid metabolites, but the precise mechanisms mediating HPV are still incompletely understood [ 15 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous experiments, a distinctive reduction of HPV was observed in lungs of endotoxemic mice [4,16]. It has been shown that HPV is modulated by several vasoactive mediators including nitric oxide and arachidonic acid metabolites, but the precise mechanisms mediating HPV are still incompletely understood [15][16][17][18][19]. Increased activity of NOS2 [13] results in elevated sGC activity with subsequent induction of the effector proteins of sGC in smooth muscle cells.…”
Section: Discussionsupporting
confidence: 83%
“…NFκB expression can by down-regulated by CO in LPS stimulated mouse peritoneal macrophages [ 37 ]. Thus, restoration of HPV by inhaled CO (iCO) in endotoxemic mice [ 38 ] might be attributable to anti-inflammatory effects of iCO via NFκB expression.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence has demonstrated that each member of this triad of gasotransmitter can influence each other. For example, the inhibition of the NO synthesis might increase the CO production [ 129 ], while low-dose CO has been showed to decrease the eNOS mRNA expression [ 130 ].…”
Section: Crosstalk Between No and The Other Gasotransmittersmentioning
confidence: 99%